Smoking behaviors and anxiety levels of 1st and 6th grade students of the medical school - Er, Tuğçe; Kurçer, Mahmet Ali (Journal of Dependence, 2020)
Objective: The aim of this study was to examine the smoking behaviors of the first and last year students of the medical faculty and to compare the nicotine addiction levels and anxiety levels.Method: A 12-item data collection form was applied to students studying in Bulent Ecevit University Medical Faculty 1st and 6th grades. In the study,21-item Beck Anxiety Inventory was used to measure anxiety levels, and a 6-question The Fagerström Test for Nicotine Dependence (FTND) was used to measure nicotine addiction level.Results: 33.0% (n=66) of the students participating in the study were smoking. Significantly higher smoking frequency was found in the sixth grades (43.3%) compared to the first grades (22.4%). 53.5% of the students (n = 107) have anxiety symptoms according to their own expressions. The anxiety point average of students who smoke is 10.27 ± 7.22, while the non-smokers is 5.11 ± 5.07. The anxiety point average of students with nicotine addiction level of 5 and above is 12.11 ± 6.52, while those of 4 and below are 8.19 ± 7.51.Conclusion: Smoking control programs should be given priority throughout medical school education, which can cause stress and anxiety symptoms.
Keywords: Cigarette; anxiety; medical school students